The Three-Dimensional Standard Framework and Industry Adaptation in Brand Marketing Informatization - Lu, Bo (Studies in Social Science & Humanities, 2025)
The rapid development of information technology has made brand marketing informatization an essential driving force for modern enterprise development. By utilizing digital means to achieve precise marketing, brand monitoring, and consumer behavior analysis, enterprises can enhance their brand influence and market competitiveness. However, existing brand marketing informatization tools, mostly designed in a generalized manner, fail to meet the specific needs of different industries. To address this issue, this paper proposes the concepts of the “Three-Dimensional Standard Framework” and the “Industry Characteristic Coefficient.” The Three-Dimensional Standard Framework covers three key dimensions: brand health monitoring, dynamic updating of consumer profiles, and cross-channel content coordination, which comprehensively cover the crucial aspects of brand marketing informatization. The Industry Characteristic Coefficient, by quantifying the special needs of different industries, enhances the targeting and effectiveness of the tools.